2019
DOI: 10.3389/fpsyg.2019.01447
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and Depression Among Early Adolescents: The Moderating Role of Parental Support

Abstract: Early adolescence is a period of development of emotional competence, but also of increasing vulnerability for the onset of depressive symptoms. While literature underscored that empathy promotes social relationships and psychological well-being over the life course, the possible role of high empathy levels as a risk factor for depression has been under investigated, especially among early adolescents. Moreover, although parenting practices are known to influence both empathy and depression in adolescence, few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 50 publications
(79 reference statements)
3
26
0
4
Order By: Relevance
“…Results suggested that those with higher personal distress showed higher level of negative emotions and lower level of positive emotions. This lends further support to linking the personal distress to internalizing symptoms ( Calandri et al, 2019 ; Neumann et al, 2016 ; Shu, Hassell, Weber, Ochsner, & Mobbs, 2017 ). Individuals who excessively share negative emotions of others may also be immersed in negative affect during COVID-19, thus experiencing depression, anxiety, and stress together with less vigor and positive emotions to some extent.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Results suggested that those with higher personal distress showed higher level of negative emotions and lower level of positive emotions. This lends further support to linking the personal distress to internalizing symptoms ( Calandri et al, 2019 ; Neumann et al, 2016 ; Shu, Hassell, Weber, Ochsner, & Mobbs, 2017 ). Individuals who excessively share negative emotions of others may also be immersed in negative affect during COVID-19, thus experiencing depression, anxiety, and stress together with less vigor and positive emotions to some extent.…”
Section: Discussionsupporting
confidence: 57%
“…Second, personal distress (alternatively labeled empathic stress) represents experience of “self-oriented” negative feelings of distress in reaction to another's state or condition ( Davis, 1983 ; Schreiter et al, 2013 ). Affective empathy may represent risk factors for depression ( Calandri, Graziano, Testa, Cattelino, & Begotti, 2019 ; MacDonald & Price, 2019 ) and anxiety ( Gambin and Sharp, 2016 , Gambin and Sharp, 2018a ) when present at extreme levels or in particular contexts. Specifically, one study claimed that no effect of empathic concern was found ( Schreiter et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite many studies highlighting a positive role of empathy with respect to adolescents’ adjustment, contrasting results emerge when considering the relationships between high levels of empathy and depressive symptoms. Although some studies suggested that deficits in empathy were related to higher depression among adolescents (Domes et al, 2016; Schreiter, Pijnenborg, & Aan Het Rot, 2013), other research suggested that also high levels of empathy might expose individuals to internalizing problems (Calandri et al, 2019). In particular, some studies found that extreme sympathy and compassion, as a response to other people’s suffering, may lead to consequent prolonged and exhausting empathic reactions or “empathic fatigue” (Oakley, Knafo, & McGrath, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is also relevant to study the teaching of social values by parents, because adolescents' social dimension is a part of their psychological adjustment, and it appears to predict future adulthood competences (Allemand et al, 2019;Calandri et al, 2019;Bloom and Lambie, 2020). Social values are understood as "criteria shared by the majority of a society in an ideal sense, all of which lead them to the better society.…”
Section: Parental Competence and Adolescencementioning
confidence: 99%